Open Surgery for Patellar Tendon Rupture and Tibial Tuberosity Avulsion Fracture in Pre-Existing Osgood Schlatter Lesion: A Case Report - Shianita Limena; Anak Agung Ngurah Ronny Kesuma; I Komang Mahendra Laksana (Journal Orthopaedi and Traumatology Surabaya)
Background: In Osgood Schlatter Disease, despite being a self-limiting disease during adolescence, various complications of Osgood Schlatter Disease could also present in adulthood. An uncommon injury pattern requires surgical treatment. This study aims to understand the implementation of surgery in managing complications case of Osgood Schlatter Disease.